Peningkatan Kapasitas Guru PAUD dalam Pengembangan Teknologi Pembelajaran di Kota Bula Seram Bagian Timur - Abednego, Abednego; Lokollo, Lamberthus Johannes; Sahalessy, Arnold (Jurnal Pengabdian Arumbai, 2024)
Early childhood education is the development of children from birth to 6 years of age, to prepare physical and spiritual growth so that they are ready to enter education. Age 0-6 years, the golden age, has a major influence on further development. Early childhood education is the key to growth. Limitations of learning technology hinder innovation. The development of learning technology needs to be effective, according to student character, and interactive. The principles of efficiency, interactivity, and teacher utilization need to be considered. The purpose of this community service is to improve the understanding and application of learning technology that is in accordance with the development of the current PAUD curriculum among PAUD teachers in Bula City. The method is carried out with Socialization and interactive discussions. The implementation of the program is scheduled for July 2023, focusing on the development of learning media for PAUD teachers. The long-term plan covers all PAUD teachers in Bula City, East Seram, with the aim of increasing their capacity in Learning Technology. The results of the activity include face-to-face meetings, demonstrations, and training in learning media. Attended by 26 PAUD teachers, discussing teacher introduction, media theory, and learning technology. Although time was limited, the goal was achieved, increasing teacher knowledge and skills. Positive evaluation, great benefits for the quality of learning.